2004
DOI: 10.1111/j.0001-7272.2004.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

crabp and maf highlight the novelty of the amphioxus club‐shaped gland

Abstract:  Abstract Jackman, W. R., Mougey, J. M., Panopoulou, G. D. and Kimmel, C. B. 2004. crabp and maf highlight the novelty of the amphioxus club-shaped gland. -Acta Zoologica (Stockholm) 85 : 91-99The club-shaped gland (csg) is a prominent organ during the development of amphioxus. However, the evolutionary significance of this pharyngeal structure has been a mystery because of the lack of an obvious corollary in vertebrates or other close relatives. To address the homology of the csg by molecular means, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The only difference between these species is that, in the chick, the signal is restricted to the caudal half of each labeled somite, a regionalisation that is not observed in amphibians and teleosts. A large Maf expression in the somites was probably already present in the common ancestor of cephalochordates and vertebrates, since the unique Amphioxus large Maf gene shares this expression territory with its vertebrate MafA and MafB counterparts (Jackman et al 2004). Taken together, these data strongly suggest that this expression territory has been retained in amphibians and actinopterygians by the MafA and MafB, but not the c-Maf and Nrl classes, and subsequently lost by the MafB class in the lineage of amniotes (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…The only difference between these species is that, in the chick, the signal is restricted to the caudal half of each labeled somite, a regionalisation that is not observed in amphibians and teleosts. A large Maf expression in the somites was probably already present in the common ancestor of cephalochordates and vertebrates, since the unique Amphioxus large Maf gene shares this expression territory with its vertebrate MafA and MafB counterparts (Jackman et al 2004). Taken together, these data strongly suggest that this expression territory has been retained in amphibians and actinopterygians by the MafA and MafB, but not the c-Maf and Nrl classes, and subsequently lost by the MafB class in the lineage of amniotes (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…CRABP-like proteins of invertebrates, such as ascidian tunicates, amphioxus, annelids, nematodes or arthropods (Fig. 4), are members of the greater FABP family [56] without exhibiting a strong phylogenetic association with vertebrate CRABPs [17]. It is hence conceivable that RA binding of FABPs was acquired specifically in the lineage leading to extant vertebrates.…”
Section: Retinol Processingmentioning
confidence: 99%
“…None of the morphology-based homologies listed in Table 1 has been widely accepted (the comparisons with the chordate mouth/ foregut or a chordate gill slit remain the best of an inconclusive lot). Finally, a recent review of developmental genetic data (Jackman et al 2004) gave no clear insights into homologies between the club-shaped gland and structures in other animals, and the authors suggested that the amphioxus club-shaped gland might be an evolutionary novelty that has arisen within the cephalochordate lineage.…”
Section: Discussionmentioning
confidence: 99%